Happy birthday, Molly! : a springtime story / 4. - Tripp, Valerie, 1951- (American girl - Molly, 2000)
When an English girl comes to stay at Molly's during World War II, she and Molly learn to bridge their differences and ultimately enjoy a wonderful, mutual birthday party.